Factors influencing the outcomes of dermatoses during the COVID-19 outbreak in China: a retrospective study - Li, Jing-Hui; Li, Si-Zhe; Wang, Si-Hang; Zhang, Jie; Xie, Ying-Han; Zuo, Ya-Gang (Frontiers in Medicine, 2024)
Background The coronavirus disease 2019 (COVID-19) pandemic subverted people’s lives and potentially affected the management and prognosis of pre-existing dermatoses. The study aims to identify factors influencing the outcomes of dermatoses during a rapid and widespread Omicron outbreak in China following the adjustment of the COVID-19 policy. Materials and methods This retrospective observational study involved outpatients visiting the dermatology department at a tertiary referral hospital in Beijing, China between December 2022 and February 2023. Demographics, COVID-19 characteristics, treatment modalities, and dermatosis outcomes were subjected to statistical analysis. Results The odds ratio (OR) for vitiligo aggravation during COVID-19 was 0.497 [95% confidence interval (CI): 0.254–0.973, p = 0.038] compared to total patients with various dermatoses. Psoriasis patients with a maximum body temperature (Tmax) over 38.6°C during COVID-19 were 2.833 times more likely to experience dermatosis aggravation (OR: 2.833 [1.029–7.803], p = 0.041). Moreover, autoimmune bullous disease (AIBD) patients receiving biologics treatment exhibited a reduced likelihood of aggravation during the COVID-19 outbreak (OR: 0 [0–0.531], p = 0.011). Conclusion Vitiligo exhibits lower aggravation rates during COVID-19 than other dermatoses. A higher body temperature during COVID-19 infection can increase the risk of psoriasis aggravation. Biologics treatment reduces the risk of AIBD aggravation during the COVID-19 outbreak.